El liderazgo institucional en el desempeño laboral del personal docente y administrativo de la universidad técnica de Cotopaxi - García Espín, Daniela Lisbeth (2022)
The purpose of the research is to know how institutional leadership affects the work performance of the teaching and administrative staff at Technical University of Cotopaxi. Also, the type of research is quantitative, because mathematical and statistical analysis tools were used to relate two variables; in addition, exploratory, descriptive and correlational research was applied. The technique used for the collection of information was the online survey, which was applied to a sample of 215 people, for the creation of the instrument was taken as a reference the book Sampling Strategies and thesis questionnaires with similar topics already applied, the same that were modified and adapted to the research topic. It was determined that within each department there is a medium-high leadership and performance, these results were obtained by using the SPSS statistical tool, which allowed analyzing each variable separately and providing a high, medium and low range, and to meet the objective of the research, the chi-square test was applied. Finally, to verify the hypothesis, the results obtained from the chi-square test were analyzed, which showed the incidence that exists between the research variables, giving a value of less than 0.05, therefore the hypothesis is accepted.